I. Asimov a memoir - Asimov, Isaac 1920-1992 (Doubleday, 1994)
But more than that, Isaac Asimov was one of the most wide-ranging minds of this century, and he earned the nickname the Great Explainer for his nonfiction works on subjects ranging from the nature of the universe to Byron's Don Juan. In these memoirs, he looks back on a long and very full life, and discusses subjects he has never before addressed. Exuberant, topically arranged, and richly anecdotal, I. Asimov shines with the author's incomparable personality